GAMBARAN PENGETAHUAN TERHADAP COVID-19 BERDASARKAN JENIS KELAMIN PADA MAHASISWA FAKULTAS KESEHATAN MASYARAKAT (Studi pada Mahasiswa Fakultas Kesehatan Masyarakat Universitas Diponegoro Angkatan 2020) - Ni Putu Desinta Naninda Carisa Putri; Moh. Arie Wurjanto; Nissa Kusariana; Ari Udijono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
At the end of 2019, precisely in December, the world was shaken by the emergence of a new virus infection (coronavirus) (Kemenkes, 2020). Coronavirus is a group of viruses that can infect humans and animals. This virus belongs to the beta group coronavirus. Educating and knowing about COVID-19 is not an easy things to do. A valid and reliable source of data and information on COVID-19 is essential. The purpose of this research is to determine the description of knowledge of 2020 Diponegoro University Faculty of Public Health students college about COVID-19. The method used in this research is descriptive methods based on solving problems based on current facts. Large sample as 94 responders. Sampling is done with simple random sampling techniques. Data is distributed with a questionnaire that contains a few questions through the google form. From the sample obtained, there are eight male (8.5%) and 86 female (91.5%) respondents. Also 70 (74.5%) respondents who had good knowledge of COVID-19 were found, 24 (25.5%) respondents have sufficient knowledge and no respondent has less knowledge. That means most of respondents, either male or female have a good knowledge about COVID-19. However, socialization is still needed for students to further enhance knowledge about COVID-19, especially for students who still have a sufficient level of knowledge.